2019
DOI: 10.1186/s12906-019-2754-7
|View full text |Cite
|
Sign up to set email alerts
|

1α, 25-dihydroxy Vitamin D3 containing fractions of Catharanthus roseus leaf aqueous extract inhibit preadipocyte differentiation and induce lipolysis in 3T3-L1 cells

Abstract: BackgroundTo investigate the potential of Catharanthus roseus leaf aqueous crude extract (CRACE) as a regulator of adipocyte development and function.Methods3T3-L1 adipogenesis model was used to investigate the effect of CRACE on adipogenesis. 3T3-L1 preadipocytes (for adipogenic differentiation) and mature 3T3-L1 adipocytes (for adipocyte function) were treated with non-toxic doses of CRACE. The outcomes were corroborated by intracellular lipid accumulation, expression of pro-and anti-adipogenic effector mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The exposure dose increased, the red color became deeper, and the fat cells were more densely distributed; WB results showed the protein expressions of CEBPα, FAS, SREBP1, and PPARγ increased in adipocytes. 3T3-L1 pre-adipocyte in vitro experiments are often used to evaluate the interference of environmental chemicals on adipogenesis, and provide a basis for environmental substances that can affect lipid metabolism in the body [5,10,24]. Studies have shown that [11,17]: 4-NP increased PPARγ activity at 1 μM, and significantly promoted triglyceride accumulation in 3T3-L1 adipocytes at 10 μM.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure dose increased, the red color became deeper, and the fat cells were more densely distributed; WB results showed the protein expressions of CEBPα, FAS, SREBP1, and PPARγ increased in adipocytes. 3T3-L1 pre-adipocyte in vitro experiments are often used to evaluate the interference of environmental chemicals on adipogenesis, and provide a basis for environmental substances that can affect lipid metabolism in the body [5,10,24]. Studies have shown that [11,17]: 4-NP increased PPARγ activity at 1 μM, and significantly promoted triglyceride accumulation in 3T3-L1 adipocytes at 10 μM.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of differentiation, there was a decrease in the level of stimulatory Lipin1 and an increase in the level of the inhibitory Kruppel-like factor (KLF7). Meanwhile, at the final stage of differentiation, there was a decrease in levels of C/EBPα, Lipin1, and other similar positive effectors such as fatty acid synthase (FAS) and sterol regulatory element binding protein 1c (SREBP1c) in the extract-treated cells (Borah et al, 2019). O n l i n e F i r s t…”
Section: Catharanthus Roseusmentioning
confidence: 99%
“…This plant is most commonly found in Java, Sulawesi, Kalimantan, and Sumatra islands. It has various benefits, especially as a medicinal plant, where various properties were identified (Borah et al, 2019;Nejat et al, 2015). Catharanthus roseus is known to have anti-diabetic, anti-microbial, anti-mutagenic, anti-mitotic, antioxidant, and anticancer effects (Nejat et al, 2015).…”
Section: Catharanthus Roseusmentioning
confidence: 99%
See 2 more Smart Citations